907. The HCV Care Continuum Among Hospitalized Persons Who Inject Opiates: Missed Opportunities for Screening and Referral to Treatment. (4th December 2021) - Kuo, Irene; Catalanotti, Jillian S; Akselrod, Hana; McGonigle, Keanan; Mai, William; Notis, Melissa; Kattakuzhy, Sarah; Brokus, Christopher J; Eaton, Ellen; Eaton, Ellen; Burgan, Kaylee W; Burkholder, Greer A; et al.
Abstract: Background: Despite an effective cure, hepatitis C virus (HCV) remains a major public health problem for persons who inject opiates. Hospitalization provides an opportunity to identify chronic HCV infection and provide referral and linkage to outpatient care upon discharge. We examined the HCV care continuum among hospitalized persons who inject drugs and have opiate use disorder (OUD). Methods: The CHOICE Study is a retrospective chart review of adults hospitalized with infectious complications of OUD and injection drug use at four academic medical centers (University of Maryland, George Washington University, University of Alabama, and Emory University). The sample included patients hospitalized between 1/1/2018-12/31/2018, had ICD9/10 diagnosis codes consistent with OUD and acute bacterial/fungal infection, and chart review verification of active infection associated with OUD. Data on HCV antibody (Ab) and RNA testing and referral to HCV treatment within the medical system were abstracted from medical records. Results: Of 287 patients, median age was 40 (IQR: 32-52), 59% were male, and 63% were white and 34% black. Overall, 38% (n=108) had known HCV infection at hospitalization; of those with unknown status, only 41% (n=73) were screened for HCV. Among those, 67% were HCV Ab+. Of patients who were HCV Ab+ or had known HCV infection (n=157), only 52% were tested for HCV RNA, of whom 61% had detectable RNA. Only 40% of those with detectable RNA received a treatment referral prior to discharge (Fig. 1). The length of stay of the admission was not associated with treatment referral, but a shorter length of stay was significantly associated with not being screened for HCV Ab or RNA tested (p< 0.05). Of five patients who were referred to care within the medical system, four initiated HCV treatment, and two achieved known sustained viral response. Figure 1. HCV Continuum of care for hospitalized patients who inject drugs with opioid use disorder (OUD) at four academic medical centers in the United States, January 2018-December 2018 Conclusion: Hospitalization is a missed opportunity for HCV screening and linkage. Despite opportunities to address HCV infection among this highly impacted population, there were sizeable gaps in the HCV continuum of care among hospitalized persons who inject opiates. Structural reasons such as length of stay may be a factor in implementing HCV testing. Disclosures: Sarah Kattakuzhy, MD, Gilead Sciences (Scientific Research Study Investigator, Research Grant or Support) Ellen Eaton, MD, Gilead (Grant/Research Support) Ellen Eaton, MD, Gilead (Individual(s) Involved: Self): Research Grant or Support Greer A. Burkholder, MD, MSPH, Eli Lilly (Grant/Research Support) Elana S. Rosenthal, MD, Gilead Sciences (Research Grant or Support)Merck (Research Grant or Support)